Efficacy and safety of bisphosphonates in pediatric glucocorticoid-induced osteoporosis: a meta-analysis and pharmacovigilance study - Xu, Xiaolin; Wang, Luquan; Yang, Mengyang; Li, Yan; Yang, Changqing; Mei, Dong; Guo, Peng; Mao, Huawei (Frontiers in Pediatrics, 2025)
ObjectivesThe prevalence of glucocorticoids (GCs) administration in pediatric populations has resulted in numerous adverse reactions, notably osteoporosis. Given its role in managing glucocorticoid-induced osteoporosis, the efficacy and safety of bisphosphonates hold considerable importance. This study conducted a meta-analysis by systematically reviewing and incorporating relevant literature on the efficacy and safety of bisphosphonates in the management of osteoporosis or bone infarction induced by GCs therapy in pediatric populations. Additionally, the analysis of potential adverse reactions was augmented by utilizing real-world data from the FAERS database. The primary objective of this study is to offer insights and guidance for the treatment of glucocorticoid induced osteoporosis in pediatric patients.MethodsA meta-analysis was performed on existing literature to assess the efficacy and safety of bisphosphonates for managing glucocorticoid-induced osteoporosis. Additionally, a retrospective pharmacovigilances study was carried out to investigate adverse reactions and medication variations in pediatric patients with glucocorticoid-induced osteoporosis, using data from the FDA Adverse Event Reporting System (FAERS) database between Q1 2004 and Q4 2023.ResultsThe meta-analysis incorporated a total of 14 articles encompassing 572 patients. The findings of this study indicate that bisphosphonate therapy is more effective in enhancing bone mineral density (BMD) and BMD Z-scores in children compared to the control group, albeit with a heightened risk of adverse reactions. Furthermore, there was no significant disparity observed between the impact of bisphosphonate treatment and control groups on fracture outcomes. Subsequently, in the ensuing Pharmacovigilance investigation, 668 instances of adverse reactions associated with bisphosphonates are analyzed. The findings indicated that the most prevalent adverse reactions, as evidenced by the highest number of positive signals were various examinations, musculoskeletal and connective tissue diseases, injuries, poisoning and operational complications, as well as systemic diseases and reactions at the administration site.ConclusionsThis study conducted a comprehensive analysis of the efficacy and safety of bisphosphonates in the treatment of osteoporosis caused by GCs use in pediatric patients, laying the groundwork for future research. Nevertheless, the constraints of retrospective studies highlight the need for additional investigation through prospective studies.